ENERGY SAVING. PIEZOGENERATORS - Nikiforov, Andrey; Kushnir, Polina (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
The object of consideration is a static generator of piezoelectric energy. The purpose of the work is to study the operation modes and designs of piezoelectric converters; selection of a suitable design for the converter; the development of the model of the converter and the determination of its output characteristics. The work is devoted to the development, research and creation of piezoelectric generator of static type. This generator can be a small independent power source of autonomous different devices of radio electronics, as it transforms the free energy of vibrations of the external environment into an electrical signal. In addition, solving problems related to strength characteristics will allow us to use this type of piezo-generators in the future under conditions of a nonlinear stress-strain state.